دور الأسرة العربية و الاتفاقيات الدولية في تكريس مبدأ التعايش السلمي بين الثقافات - بن شويخ, صارة; مساعدية, أمينة (University of Eloued جامعة الوادي, 2019)
مما لا شك فيه أن التعايش بين مختلف الثقافات مطلب إنساني، من منطلق أن الشعوب بمختلف انتماءاتها العرقية و الثقافية و الدينية و الإيديولوجية، تقوم على مبادئ مشتركة أساسها السلم و المساواة و حب الخير و نبذ التمييز و الكراهية و العنف و التطلع إلى الرقي و التطور، و ذلك إنما يتحقق بتقبل الاختلافات الموجودة بين أفراد المجتمع الواحد و استيعاب تواجد أجناس و لغات و ثقافات متباينة على إقليم الدولة الواحدة. و هذه كلها تحديات مرت بها الأسرة العربية نتيجة هجرتها نحو الدول الغربية، الأمر الذي استدعى من هذه الأخيرة السعي وراء تهيئة المحيط العام للتعايش السلمي بإصدارها لعدة اتفاقيات دولية تصب في مجملها في هذا الاتجاه Abstract : There is no doubt that the coexistence of different cultures is a human demand, based on the fact that people of different ethnic, cultural, religious and ideological backgrounds are based on common principles based on peace, equality, love of good, rejection of discrimination, hatred and violence, and the aspiration to progress and development. , And this is achieved by accepting differences between members of one society, and the absorption of the presence of different races, languages and cultures on the territory of one state. These are all challenges faced by the Arab family as a result of their emigration to Western countries. This led the latter to seek to create a general environment for peaceful co-existence by issuin1 g several international agreements that would follow in this direction
The role of the Arab family and international conventions in promoting the principle of peaceful coexistence among cultures
مجلة الدراسات والبحوث الاجتماعية المجلد 07 العدد 02 جامعة الوادي
Keywords: التعايش السلمي، الأسرة العربية، الاتفاقيات الدولية; Peaceful coexistence, Arab family, international conventions